Simple pencil‐drawn paper‐based devices for one‐spot electrochemical detection of electroactive species in oil samples. Issue 16 (9th June 2015) - Dossi, Nicolò; Toniolo, Rosanna; Terzi, Fabio; Piccin, Evandro; Bontempelli, Gino
Abstract : We propose here simple electrochemical cells assembled with electrodes pencil drawn on paper for conducting one‐spot tests enabling olive oil to be easily distinguished from other vegetable oils. They consist of small circular pads of hydrophilic paper defined by hydrophobic barriers, these last printed by using custom‐designed rubber stamps, where working, reference, and counterelectrodes are drawn by pencil leads. These cells were first wetted with a small volume of aqueous electrolyte, avoiding coating of the upper surface of electrodes. A controlled volume of edible oil samples was then applied on top of the moist cell. The results found proved that these devices can be adopted as effective platforms suitable for the detection of electroactive compounds present in edible oils. In fact, they allow voltammetric profiles to be recorded not only for the oxidation of water soluble species (ortho‐diphenols, as well as some monophenols and polyphenols) present in olive oils, but also for electroactive hydrophobic components (e.g., α‐tocopherol) present in sunflower oils, which were chosen as model of seed oils. The whole of collected findings pointed out that simple one‐spot tests performed by these devices enable olive oils to be easily distinguished from other edible oils on the basis of their clearly different voltammetric profiles. A satisfactory interdevice reproducibility (±13%) was estimated by applying strictly similar extra virgin olive oil samples onto seven different cells carefully prepared by the same procedure. An operating mechanism able to account for the detection of also electroactive hydrophobic compounds present in oils is proposed.